Camouflaging attenuated Salmonella by cryo-shocked macrophages for tumor-targeted therapy - Leyang Wu; Zengzheng Du; Lin Li; Liyuan Qiao; Shuhui Zhang; Xingpeng Yin; Xiaoyao Chang; Chenyang Li; Zichun Hua (Signal Transduction and Targeted Therapy, 2024)
Abstract Live bacteria-mediated antitumor therapies mark a pivotal point in cancer immunotherapy. However, the difficulty in reconciling the safety and efficacy of bacterial therapies has limited their application. Improving bacterial tumor-targeted delivery while maintaining biosafety is a critical hurdle for the clinical translation of live microbial therapy for cancer. Here, we developed “dead” yet “functional” Salmonella-loaded macrophages using liquid nitrogen cold shock of an attenuated Salmonella typhimurium VNP20009-contained macrophage cell line. The obtained “dead” macrophages achieve an average loading of approximately 257 live bacteria per 100 cells. The engineered cells maintain an intact cellular structure but lose their original pathogenicity, while intracellular bacteria retain their original biological activity and are delay freed, followed by proliferation. This “Trojan horse”-like bacterial camouflage strategy avoids bacterial immunogenicity-induced neutrophil recruitment and activation in peripheral blood, reduces the clearance of bacteria by neutrophils and enhances bacterial tumor enrichment efficiently after systemic administration. Furthermore, this strategy also strongly activated the tumor microenvironment, including increasing antitumor effector cells (including M1-like macrophages and CD8+ Teffs) and decreasing protumor effector cells (including M2-like macrophages and CD4+ Tregs), and ultimately improved antitumor efficacy in a subcutaneous H22 tumor-bearing mouse model. The cryo-shocked macrophage-mediated bacterial delivery strategy holds promise for expanding the therapeutic applications of living bacteria for cancer.